2014
DOI: 10.3892/ijmm.2014.1740
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin attenuates TNF-α-induced apoptosis in endothelial progenitor cells via the upregulation of SIRT1

Abstract: Abstract. Endothelial progenitor cells (EPCs) originate from the bone marrow and can be classified as either early or late EPCs. The focus of this study was on late EPCs, as they play an important role in angiogenesis and vascular proliferation. Evidence suggests that inflammatory and oxidative changes can increase EPC apoptosis. Of note, tumor necrosis factor-α (TNF-α) is a contributing risk factor to the development of atherosclerosis and plays a key role as both an inflammatory mediator and an inducer of ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 51 publications
1
39
0
Order By: Relevance
“…Indeed, many lines of evidence indicate that NOX2-derived oxidative stress reduces circulating EPCs in diabetic patients as well as hampering the neovascularization efficiency of EPCs in an experimental model of hind limb ischaemia in aged mice (Turgeon et al, 2012). Moreover, separate studies show that the pro-inflammatory cytokine TNFα also activates NOX2 and reduces the viability of endothelial cells (Frey et al, 2002; Li et al, 2005; Schroder et al, 2012) and EPCs (Du et al, 2014). Consistent with these studies, we found chronic exposure to TNFα induces NOX2 expression and decreases survival of EPCs.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, many lines of evidence indicate that NOX2-derived oxidative stress reduces circulating EPCs in diabetic patients as well as hampering the neovascularization efficiency of EPCs in an experimental model of hind limb ischaemia in aged mice (Turgeon et al, 2012). Moreover, separate studies show that the pro-inflammatory cytokine TNFα also activates NOX2 and reduces the viability of endothelial cells (Frey et al, 2002; Li et al, 2005; Schroder et al, 2012) and EPCs (Du et al, 2014). Consistent with these studies, we found chronic exposure to TNFα induces NOX2 expression and decreases survival of EPCs.…”
Section: Discussionmentioning
confidence: 99%
“…In regards to apoptotic pathways, SIRT1 activation can block external membrane PS exposure during the early phases of apoptosis in mature cells (70, 149151). SIRT1 also can counteract apoptosis initiated by tumor necrosis factor-α (TNF-α) in endothelial progenitor cells (152). Loss of SIRT1 expression in endothelial progenitor cells leads to apoptotic cell death that can occur in smokers and chronic obstructive disease patients (153).…”
Section: Circadian Clock Genesmentioning
confidence: 99%
“…SIRT1 pathways are involved in vascular survival and senescence (88, 152, 161), atherosclerosis (162166), lifespan extension (4, 167169), diabetic retinopathy (170), cellular metabolism and DM (14, 17, 20, 115, 145, 171, 172), oxidative stress pathways (58, 148, 173179), and neuronal survival and cognition (11, 113, 180183). …”
Section: Sirt1 and Non-coding Rnasmentioning
confidence: 99%
“…However, insufficient SIRT1 activity may have a detrimental affect upon vascular cell survival (23, 78, 79) and block protection against cardiovascular disease (53, 8082). Overall, SIRT1 controls multiple cellular functions that are involved with modulation of vascular survival and senescence (18, 83, 84), control of vascular tone through the transient receptor potential cation channel A1 (TRPA1) (85), development of atherosclerosis (80, 8689), extension of lifespan (42, 73, 90, 91), alterations in cellular metabolism (10, 31, 57, 9296), enhancement of neuronal survival and cognition (46, 59, 92, 97), and protection against oxidative stress (58, 81, 94, 98103). …”
Section: Sirt1 As a Target For Vascular Diseasementioning
confidence: 99%